Effect of potassium application on wheat (Triticum aestivum L.) in old Himalayan Piedmont Plain - Saha, PK; Hossain, ATMS; Miah, MAM (Bangladesh Journal of Agricultural Research, 2010)
A field trial was conducted in Rabi season 2001-2002 at the Bangladesh Agricultural Research Institute’s Agricultural Research Station (BARI ARS) farm, Thakurgaon to evaluate a higher dose of K (66 kg K/ha) for maximizing yield of wheat and sustain soil native K level for wheat in north-western (NW) region of Bangladesh. To accomplish the objective, three levels of K (T1 = K0, T2 = K66, and T3= K38 (Farmers' practice) were tested. T1= K0 and T2 = K66 were tested under soil test based (STB) N116 P15 S36 Zn1 B1.7 fertilization and these two treatments T1 and T2 were compared with the farmers' own fertilization practice N68 P24 K38 S16 Zn0B0 (T3). Results showed that the treatment (T2) i. e. K66 with STB dose produced the better yield of wheat (var. Protiva). The highest gross return of Tk. 35,610/- and the highest net-return of Tk. 30,479/- was obtained with the treatment T2 (STB). The dose of 66 kg K/ha for wheat growing in Old Himalayan Piedmont Plain (AEZ-1) was not adequate, and thus needs to be increased to maintain the soil K reserve, since there was an apparent negative balance of K in the soil with sole use of chemical fertilizers. The recommended P dose of 24 kg P/ha in wheat season created a positive balance of P. The STB dose for S and Zn @36 and 1 kg/ha, respectively, in wheat season created a positive balance of S and Zn in soil. Keywords: Potassium; fertilizer management; wheat; nutrient balance sheet. DOI: 10.3329/bjar.v35i2.5883 Bangladesh J. Agril. Res. 35(2) : 207-216, June 2010